2013
DOI: 10.1159/000348528
|View full text |Cite
|
Sign up to set email alerts
|

Single-Source Tumor Documentation - Reusing Oncology Data for Different Purposes

Abstract: SummaryWe present a path towards single-source tumor documentation established at the Comprehensive Cancer Center Erlangen-Nürnberg (CCC-EN). Our goal was to derive data for cancer quality assurance and certification, cancer registry documentation and cancer research directly from routine care documentation. Therefore, clinical documentation activities were analyzed and a cancer data superset, containing these required elements, was developed. This superset was then split into appropriate clinical documentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…The results are in line with the findings of other similar studies which showed that various data, such as disease history, tests results, final diagnosis and cancer stage, long-term adverse effects and outcomes should be recorded for cancer patients (Yu et al, 2010). In a study conducted by Ries et al (2012), the needed data were extracted from different clinical information systems and were integrated to report the patient's health status.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results are in line with the findings of other similar studies which showed that various data, such as disease history, tests results, final diagnosis and cancer stage, long-term adverse effects and outcomes should be recorded for cancer patients (Yu et al, 2010). In a study conducted by Ries et al (2012), the needed data were extracted from different clinical information systems and were integrated to report the patient's health status.…”
Section: Discussionsupporting
confidence: 87%
“…For example, the results of Scicotte et al,'s study (2016) showed that the use of electronic medical records in outpatient cancer centers could help to improve the flow of information and reduced the average waiting time. In another study, the interest of clinicians in using oncology electronic medical records has been highlighted (Ries et al, 2012) or an oncology information system has been developed to record cancer data electronically (Yu et al, 2010). It seems that collecting cancer care data electronically has a number of benefits for patients, clinicians and policy makers and can be regarded as an important tool for improving quality of care, making informed decisions, saving costs and reducing time for patient care.…”
Section: Discussionmentioning
confidence: 99%
“…A more comprehensive approach would be to implement a "single source" documentation strategy, in which all data elements required both for routine care as well as associated research projects are entered in the EHR, and research data is consecutively extracted [10,11]. As such, the "single source" strategy would mostly be a "replacement" (of a previous, less comprehensive and flexible EHR) strategy, while trying to minimise documentation efforts by providing a single "all-purpose" EHR, without, however, restricting the scope of data a priori as a "minimal add-on" strategy necessarily would.…”
Section: General Options For Setting Up a Disease Registrymentioning
confidence: 99%
“…Although most university hospitals already implemented commercial hospital information systems and started to develop comprehensive EHRs, there is still a gap between clinical care and using this data for medical research that needs to be filled (10, 11). Recent studies have focused on providing routine clinical data for research purposes, e.g., by using a single-source tumor documentation or supporting systems for patient recruitment into clinical trials in the field of radiation oncology (12) and intensive care (13). …”
Section: Introductionmentioning
confidence: 99%